PERLINDUNGAN HUKUM TERHADAP KONSUMEN ATAS PELAYANAN DAN JASA PRAKTIK TUKANG GIGI DI KOTA PEKANBARU - Bilqis, Maharani; Bachtiar, Maryati; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Legal protection against consumers is an attempt to protect the use of an item and / or service.Consumers are persons who use goods and / or services that have the right to obtain comfort andsecurity in the use of goods and / or services. Corporate actors are persons who provide goods and / orservices that are responsible to consumers who are harmed by the corporate actor. Problems that occurwith dental services in the city of Pekanbaru, consumers do not receive services that meet the standardsof dental work.The purpose of this document is to determine the legal protection of consumers of dental servicesand the responsibility of dental professionals for the rights of consumers of dental services that are notmet.This type of research is classified according to the type of sociological research, as the authors inthis study conducted a study in the city of Pekanbaru, while the population and samples were all partiesthat were related to the problems studied in this study. Data sources used were primary data, secondarydata and tertiary data. Data collection techniques in this study with observations, interviews and librarystudies, which are information obtained from data in the field.From the results of the study, two main points can be derived. First, the state's legal effortstowards consumers and business operators are the issuance of Consumer Protection Law No. 8 of 1999in order to reconcile the position of consumers with the business community. In addition to the 2014issue of PERMENKES number 39 for consultation, monitoring and licensing, Dental Work includes therights and responsibilities of consumers as patients of dental professionals and dental professionals astraders. Secondly, dental tradespeople act as business actors for the services provided, so thatconsumers can be protected from practices that may result in losses that are subject to administrativesanctions in the event of a breach of contract, temporary termination or permanent termination. Author'ssuggestion: Firstly, there are regular instructions for dental craftsmen by the local government, theHealth Department of the city of Pekanbaru. Secondly, it is recommended that consumers actively seekinformation before using the services of dental professionals, as dentists differ from dentists. Third,dental craftsmen act as business operators to carry out their activities in accordance with applicablelaws and regulations.Keywords: Dental Builders – Consumer - Legal